Palliative dialysis: Addressing the need for alternative dialysis delivery modes. Issue 5 (2nd June 2019) - Tentori, Francesca; Hunt, Abigail; Nissenson, Allen R.
Abstract: For some patients with kidney failure, particularly those who have limited life expectancy or severe comorbidities, the "standard" dialysis treatment regimen may be perceived as excessively burdensome and may not align well with the patient's own priorities. For such patients, a palliative approach to the provision of dialysis—whereby treatment is tailored to the needs of the individual so as to optimize quality of life and minimize disease‐related symptoms, but limit treatment burden—might offer a way to better align the delivery of care with the life goals of the patient. Here, we discuss the fundamental principles of palliative dialysis: the patients who might most benefit from this approach, treatment strategies and considerations for implementation, as well as potential barriers to its provision.